AGE AND CAUSES OF CANCER AND NON-CANCER HYSTERECTOMY AMONGST HINDU AND MUSLIM PATIENTS - Kashyap, V; Sharma, S (Indian Journal of Community Health, 2013)
Background: Hysterectomy is the second most common surgical procedure in women other than cesarean delivery but there is relatively little information about its causes in relation to religions. Objective: To find out the causes of hysterectomy in relation to age and parity amongst Hindu and Muslim patients Methods: 1000 records of the patients, who underwent cancer hysterectomy due to cervical cancer or non-cancer hysterectomy for benign conditions of the uterus in past years of their life, were analyzed. All patients were from the same hospital and recently visited the hospital for follow-up checkup through Pap smear. Chi square test was employed to test the association. Results: Amongst 1000 hysterectomies 570 (57%) were for carcinoma cervix and 430 (43%) for benign conditions of uterus. 485 (85%) cancer cases were Hindu and 85(15%) were Muslim, however 310 (72%) cases of benign uterine conditions were Hindu in comparison to 120 (28%) Muslim. Majority of hysterectomy cases of both the religions belonged to age group of 41-50 yrs., however, the association between the age groups and benign uterine conditions (Uterine fibroids Vs. Others) was observed highly significant in Hindu patients only. Conclusion: The study revealed that fifth decade (41-50 yrs) of life of women was found prevalent for hysterectomy in both the religions, however carcinoma cervix was more common in Hindu patients. Prolapse uterus and Pelvic Inflammatory disease were comparable high for non-cancer hysterectomy in Muslim patients.